Многостаночное обслуживание в машиностроении - Лещенко М. И. Михаил Иванович; Таурит Г. Э. Георгий Эдуардович; Гонта Ю. В. Юрий Васильевич; Василюк Г. Д. Георгий Дмитриевич (Киев, Технiка, 1987)
Авт. указаны перед вып. дан.